2022
DOI: 10.3390/su14020909
|View full text |Cite
|
Sign up to set email alerts
|

The Drivers and Barriers of Corporate Social Responsibility: A Comparison of the MENA Region and Western Countries

Abstract: (1) Although numerous articles have been published to address the drivers or barriers of corporate social responsibility (CSR), some parts of the world have received less attention. In this study, I reviewed the literature from 2010 to 2021 to identify drivers and barriers of CSR in the Middle East and North Africa (MENA) region and compare them with the findings in Western countries. (2) Methods: For this study, I used a structured literature review method. By setting the inclusion and exclusion criteria, onl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 54 publications
0
17
0
4
Order By: Relevance
“…In addition, many studies have noted a problem with the implementation of CSR (Lentner et al, 2015;Valenti, Carden, & Boyd, 2014) and other related difficulties that have been discovered, such as limited knowledge of corporate leaders and organizations (Bjerregaard & Lauring, 2013;Wickert & De Bakkar, 2015). Alizadeh (2022) revealed in his research about barriers to CSR in the Mena Region and Western countries' lack of CSR awareness and knowledge. Bonsu (2018) also claimed that knowledge and a clear understanding of the implementation of CSR would lead to social variations.…”
Section: The Research Gapmentioning
confidence: 99%
“…In addition, many studies have noted a problem with the implementation of CSR (Lentner et al, 2015;Valenti, Carden, & Boyd, 2014) and other related difficulties that have been discovered, such as limited knowledge of corporate leaders and organizations (Bjerregaard & Lauring, 2013;Wickert & De Bakkar, 2015). Alizadeh (2022) revealed in his research about barriers to CSR in the Mena Region and Western countries' lack of CSR awareness and knowledge. Bonsu (2018) also claimed that knowledge and a clear understanding of the implementation of CSR would lead to social variations.…”
Section: The Research Gapmentioning
confidence: 99%
“…Previous studies have found that consumers do not clearly understand CSR (Öberseder et al, 2014) and CE (Sijtsema et al, 2020). Often, companies themselves lack an understanding of CSR (Alizadeh, 2022; Mahmood et al, 2021; Zou et al, 2021) and CE (Sarja et al, 2021). Likewise, business scholars, entrepreneurs, and managers often have a narrow understanding of the concept of CSR (Hoque et al, 2018).…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…Companies carry out corporate social responsibility activities to gain competitiveness, generate wealth, respond to the demands of society and support individuals and society (Benitez et al 2020). These activities are mainly focused on internal/external issues such as employees' work-life balance, employee needs, workplace safety, sustainability, human resource management, the environment, poverty and community development (Alizadeh 2022).…”
Section: ) Introductionmentioning
confidence: 99%